Patient, informal caregiver and care provider acceptance of a hospital in the home program in Ontario, Canada - Zhang Wei; Martin Carmel M; Armstrong Catherine; Dahrouge Simone; Hogg William E; Lemelin Jacques; Dusseault Jo-Anne; Parsons-Nicota Joy; Saginur Raphael; Viner Gary (BMC, 2007)
Abstract Background Hospital in the home programs have been implemented in several countries and have been shown to be safe substitutions (alternatives) to in-patient hospitalization. These programs may offer a solution to the increasing demands made on tertiary care facilities and to surge capacity. We investigated the acceptance of this type of care provision with nurse practitioners as the designated principal home care providers in a family medicine program in a large Canadian urban setting. Methods Patients requiring hospitalization to the family medicine service ward, for any diagnosis, who met selection criteria, were invited to enter the hospital in the home program as an alternative to admission. Participants in the hospital in the home program, their caregivers, and the physicians responsible for their care were surveyed about their perceptions of the program. Nurse practitioners, who provided care, were surveyed and interviewed. Results Ten percent (104) of admissions to the ward were screened, and 37 patients participated in 44 home hospital admissions. Twenty nine patient, 17 caregiver and 38 provider surveys were completed. Most patients (88%-100%) and caregivers (92%-100%) reported high satisfaction levels with various aspects of health service delivery. However, a significant proportion in both groups stated that they would select to be treated in-hospital should the need arise again. This was usually due to fears about the safety of the program. Physicians (98%-100%) and nurse practitioners also rated the program highly. The program had virtually no negative impact on the physician workload. However nurse practitioners felt that the program did not utilize their full expertise. Conclusion Provision of hospital level care in the home is well received by patients, their caregivers and health care providers. As a new program, investment in patient education about program safety may be necessary to ensure its long term success. A small proportion of hospital admissions were screened for this program. Appropriate dissemination of program information to family physicians should help buy-in and participation. Nurse practitioners' skills may not be optimally utilized in this setting.